2023
DOI: 10.3390/nu15051082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 16-Week Digital Intervention on Sports Nutrition Knowledge and Behavior in Female Endurance Athletes with Risk of Relative Energy Deficiency in Sport (REDs)

Abstract: Female endurance athletes are considered a high-risk group for developing Relative Energy Deficiency in Sport (REDs). Due to the lack of educational and behavioral intervention studies, targeting and evaluating the effects of the practical daily management of REDs, we developed the Food and nUtrition for Endurance athletes—a Learning (FUEL) program, consisting of 16 weekly online lectures and individual athlete-centered nutrition counseling every other week. We recruited female endurance athletes from Norway (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 74 publications
1
12
1
Order By: Relevance
“…Despite a tailored curriculum, one-on-one sessions partnered with group lectures did not consistently improve dietary habits in adult athletes [43]. More recently, a 16-week intervention of weekly online lectures and nutrition counselling every second week improved sports nutrition knowledge and suggested weak evidence for improved sports nutrition behaviour in female endurance athletes with symptoms of Relative Energy Deficiency Syndrome [44]. Athletes in the current study ranked their preference for solely online delivery of NE as low.…”
Section: Format and Facilitator Preferencescontrasting
confidence: 61%
“…Despite a tailored curriculum, one-on-one sessions partnered with group lectures did not consistently improve dietary habits in adult athletes [43]. More recently, a 16-week intervention of weekly online lectures and nutrition counselling every second week improved sports nutrition knowledge and suggested weak evidence for improved sports nutrition behaviour in female endurance athletes with symptoms of Relative Energy Deficiency Syndrome [44]. Athletes in the current study ranked their preference for solely online delivery of NE as low.…”
Section: Format and Facilitator Preferencescontrasting
confidence: 61%
“…For example, less than half of coaches and physicians surveyed were able to identify the three components of the female athlete triad147 148 150 151; other studies reported similar knowledge gaps among physiotherapists and athletic trainers 142 145. Short-term education programmes, using various delivery methods and focusing on factors associated with EDs, DE behaviours, and REDs have been shown to improve nutritional knowledge and reduce signs of dieting and body image concerns in female and male athletes 70 152–158. Furthermore, early identification of symptoms using screening instruments, individual health interviews and objective assessment of REDs biomarkers may be useful as secondary prevention 25.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, habits may take more than sixteen weeks to change ( 61 ) and we have previously emphasized the complexity of improving eating habits in this group of athletes ( 36 ). Since the increase in energy intake was modest among FUEL athletes (138 ± 453 kcal/day, corresponding to an increase of only 5%) ( 36 ), it may have been insufficient for improving REDs related symptoms in some of the athletes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the FUEL intervention group completed a 6- and 12-months follow-up answering the LEAF-Q, the EDE-Q, and the EAI. Other assessments included in the study, including diet and training log, has previously been described and analyzed ( 36 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation